ABC–ABC‐Type Directly meso–meso Linked Porphyrin Dimers. Issue 2 (20th December 2018) - Higashino, Tomohiro; Kurumisawa, Yuma; Iiyama, Hitomi; Imahori, Hiroshi
Abstract: Invited for the cover of this issue is the group of Hiroshi Imahori at Kyoto University. The image depicts an artistic representation of the evolution from porphyrin monomers to a porphyrin dimer. Read the full text of the article at10.1002/chem.201805405 . Abstract : " We believe that our strategy opens up new avenues for highly functionalized meso–meso directly linked porphyrin dimers in various fields ." Read more about the story behind the cover in the Cover Profile and about the research itself on page 538 ff. (DOI:10.1002/chem.201805405 ).